2011
DOI: 10.1177/1049909111420859
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Reiki Therapy on Pain and Anxiety in Patients Attending a Day Oncology and Infusion Services Unit

Abstract: Reiki is a system of natural healing techniques administered by laying of hands and transferring energy from the Reiki practitioner to the recipient. We investigated the role of Reiki in the management of anxiety, pain and global wellness in cancer patients. Building on the results of a pilot project conducted between 2003 and 2005 by a volunteer association at our hospital, a wider, 3-year study was conducted at the same center. The volunteer Reiki practitioners received 2 years of theory and practical traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 5 publications
4
60
0
11
Order By: Relevance
“…A study with cancer patients showed that Reiki is not effective on pain (Olson et al, 2003). A study showed that to Reiki reduction of 50% in mean scores of pain after each chemotherapy treatment (Birocco et al, 2012). Another study reported that Reiki decreased pain, depression, and anxiety in chronically ill people (Dressin and Singg, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A study with cancer patients showed that Reiki is not effective on pain (Olson et al, 2003). A study showed that to Reiki reduction of 50% in mean scores of pain after each chemotherapy treatment (Birocco et al, 2012). Another study reported that Reiki decreased pain, depression, and anxiety in chronically ill people (Dressin and Singg, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…There was not a statistically effective in the pilot group (Potter, 2007). Birocco et al (2012) found that the sessions were considered helpful to improve well-being (70%), relaxation (88%), pain relief (45%), sleep quality (34%), and reduce anxiety. Reiki seems to be a promising aid in anxiety control, with a marked reduction in the mean score after each treatment and a decrease of one third after 4 treatments.…”
Section: Effect Of Reiki On Anxiety Depressionmentioning
confidence: 99%
“…Pain reduction of 50% in mean scores after each treatment. The statistical significance between the first and the fourth treatment (Birocco et al, 2012). Lee et al (2008) conducted a systematic review of RCTs for the purpose of investigating whether Reiki is beneficial for pain management.…”
Section: Effect Of Reiki On Painmentioning
confidence: 99%
See 2 more Smart Citations